A mixed methods systematic literature review of barriers and facilitators to help-seeking among women with stigmatised pelvic health symptoms - Clare Jouanny; Purva Abhyankar; Margaret Maxwell (BMC Women's Health, 2024)
Abstract Background Women’s pelvic health is a globally important subject, included in international and United Kingdom health policies, emphasising the importance of improving information and access to pelvic health services. Consequences of pelvic symptoms are intimate, personal, and varied, often causing embarrassment and shame, affecting women’s quality of life and wellbeing. AIM To understand the experience of seeking healthcare for stigmatised pelvic health symptoms by synthesising all types of published primary research and mapping the results to behavioural theory, to identify potential targets for intervention. Methods Systematic search of MEDLINE, CINAHL, PsycINFO, SocINDEX, PubMED databases, CDSR and CENTRAL registers, from inception to May 2023 for all types of research capturing women’s views and experiences of seeking help with stigmatised urogenital and bowel symptoms. Studies only reporting prevalence, predictors of help-seeking, non-health related help-seeking, or written in languages other than English, German, French, Spanish and Swedish were excluded. Reference checking and forward citation searching for all included studies was performed. A results-based synthesis approach was used to integrate quantitative and qualitative data. Themes were mapped to the Common-Sense model and Candidacy framework. The Mixed Methods Appraisal Tool was used for critical appraisal. Grading of Recommendations Assessment, Development and Evaluation - Confidence in Evidence from Reviews of Qualitative research for assessing certainty of review findings. Results 86 studies representing over 20,000 women from 24 high income countries were included. Confidence was high that barriers to help-seeking were similar across all study types and pelvic symptoms: stigma, lack of knowledge, women’s perception that clinicians dismissed their symptoms, and associated normalising and deprioritising of low bother symptoms. Supportive clinicians and increased knowledge were key facilitators. Conclusions Using the Common-Sense Model to explore women’s help-seeking behaviour with stigmatised pelvic symptoms reveals problems with cognitive representation of symptom identity, emotional representations of embarrassment and shame, and a subjective norm that women believe their symptoms will be trivialised by clinicians. Together these barriers frustrate women’s identification of their candidacy for healthcare. Addressing these issues through behavioural change interventions for women and clinicians, will help to achieve universal access to pelvic healthcare services (United Nations Sustainable Development Goal 3.7). Systematic Review Registration PROSPERO CRD42021256956.